Relationship Between IPSS (International Prostatic Symptomatic Score) and Quality of Life in Patients with LUTS (Lower Urinary Tract Symptoms) - Irfansyah; Didit Pramudhito (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2019)
ABSTRACT Introduction. Lower urinary tract symptoms (LUTS) is the most common problem in men with age and can reduce quality of life due to various complaints on micturition. Method. This study was a cross sectional study conducted in May-July 2018 at the Urology Outpatient Clinic, Dr. Mohammad Hoesin Hospital Palembang and 36 samples were obtained. The technique of data collection was done by filling out the questionnaire. Analysis of data in the form of descriptive for general characteristics and correlation analysis used is the Spearman Rank test correlation. Results: The most prevalence of benign prostate hyperplasia (BPH) occurred in the age group 71-80 years as many as 12 patients (33.3%). BPH patients who came with the most LUTS experienced severe degrees of International Prostatic Symptomatic Score (IPSS) (24 patients, 66.7%). There were 16 patients (44.4%) felt their quality of life was very poor. Spearman Rank correlation test showed no significant relationship between IPSS with the quality of life of patients with BPH with LUTS (p> 0.05, r = 0.073) Conclusion. There was no significant relationship between IPSS with the quality of life of BPH patients with LUTS.